Trends in Quinoa Adoption in Marginal Areas, Economic Viability, and Policy Outlook - Hayatullah Ahmadzai (Journal of Agribusiness and Rural Development, 2020)
Global demand for quinoa has substantially grown seemingly due to the rich nutritional ingredients in quinoa grain and its resilience to unfavorable and harsh biotical stresses and environmental factors prevalent in marginal environments. Research evidence suggest that global quinoa production as well as the number of quinoa-producing countries have been substantially increased throughout the last few years. With intensive research trails and tests underway in new countries across the world, especially in the Middle East and North Africa (MENA) region, researchers and policymakers are determined to upscale its commercial production. However, little is known about its economic viability to substantiate the adoption and ultimately the sustainability of quinoa production. The economic analysis carried out in this study suggests that quinoa can be highly profitable, but its economic viability largely depends on the availability of high-yielding verities, best management practices through demand-driven extension services, and reliable market information on local demand and prices. Under the most-likely production scenario, estimated net profit can reach up to AED 6,059 ($1,651) per hectare. Given the lack of quality data, the estimated net gains are simulated to assess the level of sensitivity due to potential uncertainties and volatility in key variables and assumptions. After 10,000 iterations, the results from Monte Carlo simulation reveals that the average value of simulated net gains is about AED 8,265 per hectare with no significant chances of negative profits.